Preaching to the choir - Merrill, Hugh; Ganson, Adelia (Kansas City, Missouri : Chameleon Press, 2017)
Hugh Merrill has been a prominent activist in community art, and a respected artist and teacher at the cutting edge of Printmaking for many years. This book, written in conjunction with Adelia Ganson, brings together his writings and thoughts about printmaking, and its place in the contemporary visual arts, since the mid-1960s. It includes references to the most important developments in Printmaking in the USA as it has evolved into a major force in the visual arts and community activism. Although titled Preaching to the Choir it is also an open invitation to any artists seeking to redefine their position in the arts world to join that choir and to sing out loud and clear through the making of art that refuses to toe the line. Provocative, tantalising and encouraging by turns, this important book opens out a crucially important dialogue between artists and the community as we emerge into the dangerous light of the 21st century. For anyone wary of the machinations of the art establishment that has sold its soul to big money, the book will be a clarion call to work for and to believe in the wider values of making and sharing art.
-- First etching -- Beyond postprint -- Educating the next generation of printmakers -- What is a Quisling? : existing in the margins -- Patterns and dissent in print : placing the outlaw printmakers in historical context -- Guns, gals and gore in America : Tom Huck's evil prints -- Mel Chin draws a sausage -- Creativity as content : interview with Jim Leedy.
Includes works by Hugh Merrill, Emmett Merrill, Frances Myers, Melanie Yazzie, Jenny Schmid, Michael Krueger, and Tom Huck.
Keywords: Merrill, Hugh; Ganson, Adelia; Leedy, Jim; Prints, American; Printmakers -- United States; Prints, Abstract -- United States